2019
DOI: 10.1186/s12905-019-0814-2
|View full text |Cite
|
Sign up to set email alerts
|

Number of parity is associated with low-grade albuminuria in middle-aged and elderly Chinese women

Abstract: Background Women with a higher number of pregnancies have a higher risk of developing cardiovascular diseases. Subtle fluctuations in albumin excretion could be related to pathophysiologic changes in the vascular system. We aimed to investigate the possible association of parity with low-grade albuminuria. Methods We conducted a community-based study in 6495 women aged 40 years or older. Low-grade albuminuria was defined according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The biomarkers of cardiovascular disease are also higher owing to parity. A gradual increase in low-grade albuminuria (protein in urine, a marker of an increased risk of cardiovascular health problems) with parity was observed in women from China [42]. Giving birth early (at less than 20 years of age) also contributes to a greater overall cardiovascular risk in older age [43].…”
Section: Does Reproduction Have a Long-term Negative Impact? Health And Age-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomarkers of cardiovascular disease are also higher owing to parity. A gradual increase in low-grade albuminuria (protein in urine, a marker of an increased risk of cardiovascular health problems) with parity was observed in women from China [42]. Giving birth early (at less than 20 years of age) also contributes to a greater overall cardiovascular risk in older age [43].…”
Section: Does Reproduction Have a Long-term Negative Impact? Health And Age-related Diseasesmentioning
confidence: 99%
“…Parity is related to increased body weight. In China, women with high parity had an increased BMI, waist circumference, systolic blood pressure, fasting plasma glucose and insulin, and decreased high-density lipoprotein cholesterol [42]. In British women, the number of children was positively associated with a BMI and waist–hip ratio [44].…”
Section: Does Reproduction Have a Long-term Negative Impact? Health And Age-related Diseasesmentioning
confidence: 99%
“…Some studies suggested that parity was remarkably associated with the risk of carotid atherosclerotic plaque, and also associated with a decrease of HDL-C and an increase of the ratio of blood glucose/insulin [ 20 , 21 ]. In addition, multiple parturition could increase the risk of metabolic syndrome in women, and thus, it might result in the increased risk of ICVD in postmenopausal women to a certain extent [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate logistic analysis revealed that the OR values of parity, exposure to second (third)-hand smoke, depression, and Type D personality were 3.795 (95%CI: 1.657-8.689), 2.886 (95%CI: 1.087~7.659), 1.193 (95% CI: 1.072~1.328), and 1.148 (95%CI: 1.044~1.264), respectively, which were all risk factors for ICVD in postmenopausal women. Some studies suggested that parity was remarkably associated with the risk of carotid atherosclerotic plaque, and also associated with a decrease of HDL-C and an increase of the ratio of blood glucose/insulin (20,21). In addition, multiple parturition could increase the risk of metabolic syndrome in women, and thus, it might result in the increased risk of ICVD in postmenopausal women to a certain extent (22,23).…”
Section: Analysis Of Factors Affecting the Risk Of Icvd In Postmenopa...mentioning
confidence: 99%